Creation of composite scintillators with a short decay time - Krech, A.V.; Kofanov, D.O.; Khromiuk, I.F.; Okrushko, O.M.; Gerasymov, Ia.V.; Karavaeva, N.L.; Levchuk, L.G.; Popov, V.P.; Khabuseva, S.U. (Problems of Atomic Science and Technology, 2023)
To date, LuAG:Ce crystals are one of the most common scintillators, since they have been known for a long time and there are technologies for mass production of large-volume crystals. However, the scintillation properties of such crystals can be improved by creating mixed crystals with the replacement of some ions by others. In this work, composite scintillators based on the grown LuYAG:Ce inorganic crystals were produced. For the obtained samples, studies of optical transmission, luminescence, light output, and decay time were carried out. The optimal conditions and sizes of crystalline grains for the creation of composite scintillators have been determined. На сьогодні кристали LuAG:Ce є одними з найпоширеніших сцинтиляторів, оскільки вони відомі вже багато часу та існують технології масового виробництва великих об’ємних кристалів. Однак сцинтиляційні властивості таких кристалів можна покращити шляхом створення змішаних кристалів із заміщенням одних іонів іншими. У роботі були створені композиційні сцинтилятори на основі вирощених неорганічних кристалів LuYAG:Се. Для отриманих зразків були проведені дослідження оптичного пропускання, люмінесценції, світлового виходу та часу згасання. Встановлено оптимальні умови та розміри кристалічних гранул для створення композиційних сцинтиляторів.